Contribution To The Study Of Traditional Agro-Forestry Systems In The Oecusse District - Martins, Edmundo; Shahidian, Shakib; Nunes, Nuno (CV RIFAINSTITUT, 2024)
This work aims to contribute to the study of traditional agro-forestry systems in Oecusse, describing them in terms of composition, social organization, and cultural techniques. Existing problems in the exploitation of these systems, their geographical location, and possible guidelines for the evolution of traditional agro-forestry systems are identified. An inquiry method through interviews with farmers about agro-forestry systems was employed. Official documents, particularly region maps, were consulted to study traditional agro-forestry systems in the Oecusse district. Agro-forestry systems in Oecusse are characterized by a limited production area, low productivity of cultivated species, random distribution of plants without organization in any type of lines or patterns, and component crops of the system requiring minimal cultural care. The two types of traditional agro-forestry systems in Oecusse can be classified into the categories of agro-silvo-pastoral, agro-silvicultural, and agro-silvo-livestock. There are 44 species represented in most traditional agro-forestry farms in the Oecusse district. The traditional agro-forestry systems in the Oecusse district with Sesbania grandiflora, belonging to the leguminous family, offer advantages such as improving soil fertility, increasing water retention capacity, serving as green forage for animals, and providing firewood for self-consumption.